A Multiscale X‐Ray Tomography Study of the Cycled‐Induced Degradation in Magnesium–Sulfur Batteries. Issue 5 (31st March 2021) - Du, Wenjia; Hao, Zhangxiang; Iacoviello, Francesco; Sheng, Lin; Guan, Shaoliang; Zhang, Zhenyu; Brett, Daniel J. L.; Wang, Feng Ryan; Shearing, Paul R.
Abstract: Rechargeable Mg/S batteries have the potential to provide a compelling battery for a range of applications owing to their high capacity and gravimetric energy density, safety, and low‐cost construction. However, the Mg/S energy storage is not widely developed and deployed due to technical challenges, which include short cycle lifespan and lack of suitable electrolyte. To study the microstructure degradation of Mg/S batteries, multiscale X‐ray tomography, an inherently nondestructive method, is performed on dismantled Swagelok Mg/S cells comprising a graphene–sulfur cathode and a super‐P separator. For the first time, 3D microstructure visualization and quantification reveal the dissolution (volume fraction decreases from 13.5% to 0.7%, surface area reduces from 2.91 to 1.74 µ m 2 µ m −3 ) and agglomeration of sulfur particles, and the carbon binder densification after 10 cycles. Using tomography data, the image‐based simulations are then performed. The results show that the insoluble polysulfides can inevitably block the Mg 2+ transportation via shuttle effect. The representative volume should exceed 8200 µm 3 to represent bulk cathode. This work elucidates that the Mg/S cell performance is significantly affected by microstructural degradation, and moreover demonstrates how multiscale and multimodal characterization can play an indispensable role in developing and optimizing the Mg/S electrode design. Abstract : For the first time, high‐resolution nanoscale X‐ray tomography provides an opportunity to observe the microstructural evolution of the cathode of an Mg/S cell. The dissolution of sulfur, the densification of the carbon binder domain, and pore agglomerations over early life cycling, are considered as mainly responsible for the cathode degradation and subsequent cell failure.